2016
DOI: 10.1108/pijpsm-10-2015-0119
|View full text |Cite
|
Sign up to set email alerts
|

An empirical test of the influence of society at large on police integrity in a centralized police system

Abstract: Purpose – The purpose of this paper is to test the theory of police integrity, particularly its fourth dimension, on a centralized police agency and to assess the degree to which levels of police integrity are related to the characteristics of the larger environment. Design/methodology/approach – In 2008, a stratified representative sample of 945 Croatian police officers from ten police administrations evaluated 11 hypothetical scenarios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Few studies examine the intersectional nature of organizational, environmental, and individual factors and how each shape police integrity. In fact, across the dozens of studies on police integrity, only a small sample examine these factors through a more nuanced analytical approach (see Ivković, 2012; Ivković, Mraović, & Borovec, 2016b; Ivković, Peacock, & Haberfeld, 2016; Ivković & Sauerman, 2016; Kane & White, 2009; Lobnikar et al, 2016; Pagon, Lobnikar, & Anelj, 2004; Torstensson-Levander & Ekenvall, 2003; Vallmüür, 2016; Wolfe & Piquero, 2011). What follows is a brief overview of the state of research concerning the individual, organizational, and environmental factors.…”
Section: Determinants Of Police Integrity: a Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Few studies examine the intersectional nature of organizational, environmental, and individual factors and how each shape police integrity. In fact, across the dozens of studies on police integrity, only a small sample examine these factors through a more nuanced analytical approach (see Ivković, 2012; Ivković, Mraović, & Borovec, 2016b; Ivković, Peacock, & Haberfeld, 2016; Ivković & Sauerman, 2016; Kane & White, 2009; Lobnikar et al, 2016; Pagon, Lobnikar, & Anelj, 2004; Torstensson-Levander & Ekenvall, 2003; Vallmüür, 2016; Wolfe & Piquero, 2011). What follows is a brief overview of the state of research concerning the individual, organizational, and environmental factors.…”
Section: Determinants Of Police Integrity: a Literature Reviewmentioning
confidence: 99%
“…For instance, Vallmüür (2016) found that while female officers were more willing to report misconduct, when the behavior related to inappropriate use of force, male officers were more willing to report misconduct involving the misuse of the position for personal gain. Specific to perceptions of seriousness, there is evidence suggesting that female officers tend to view the misconduct described in the scenarios as more serious than male officers (Ivković et al, 2016b; Vallmüür, 2016).…”
Section: Individual Dynamicsmentioning
confidence: 99%
See 3 more Smart Citations